Rehabilitation effects on gully sediment yields and vegetation in a savanna rangeland. Issue 5 (5th February 2021) - Koci, Jack; Wilkinson, Scott N.; Hawdon, Aaron A.; Kinsey‐Henderson, Anne E.; Bartley, Rebecca; Goodwin, Nicholas R.
Abstract: Gully rehabilitation can contribute to catchment management by stabilizing erosion and reducing downstream sediment yields, yet the globally observed responses are variable. Developing the technical basis for gully rehabilitation and establishing guidelines for application requires studies that evaluate individual rehabilitation measures in specific environments. An eight‐year field experiment was undertaken to evaluate sediment yield and vegetation responses to several gully rehabilitation measures. The rehabilitation measures aimed to reduce surface runoff into gully head cuts, trap sediment on gully floors and increase vegetation cover on gully walls and floors. The study occurred in a savanna rangeland in northeast Australia. Two gullies were subject to treatments while four gullies were monitored as untreated controls. A runoff diversion structure reduced headcut erosion from 4.3 to 1.2 m 2 yr −1 . Small porous check dams and cattle exclusion reduced gully total sediment yields by more than 80%, equivalent to a reduction of 0.3 to 2.4 t ha −1 yr −1, but only at catchment areas less than 10 ha. Fine sediment yields (silt and clay) were reduced by 7 and 19% from the two treated gullies, respectively. The porous check dam deposits contained a lower percentage of the fine fraction than the parent soil. Significant regeneration of gully floor vegetation occurred, associated with trapping of organic litter and fine sediment. Increases in vegetation cover and biomass were comprised of native perennial grasses, trees and shrubs. In variable climates, long‐term gully rehabilitation will progress during wetter periods, and regress during droughts. Understanding linkages between rehabilitation measures, their hydrologic, hydraulic and vegetation effects and gully sediment yields is important to defining the conditions for their success. Abstract : Photographs of a gully porous check dam: (i) following installation in November 2010; (ii) during a runoff event in December 2010; (iii) at the end of the wet season in May 2013; and (iv) during the wet season in February 2018.